Digital transformation of educational content in the pedagogical higher educational institution - V. Vinokurova, Natalja (2021)
The article is aimed at researching the content of education getting transformed under the influence of digitization in the pedagogical higher educational institution. Methodologically the research was supported by various theoretical and empirical methods including pedagogical observation, analysis and design, survey data analysis and interpretation. As a result of the study qualitative changes in the following aspects of the educational system have been characterized: content of education, system for assessing the planned learning outcomes, skills of the academic teaching staff, and educational environment. The principal lines of action in acquiring, controlling one's personal information field, and using them jointly in the process of putting the interaction system “teacher – digital information environment – student” into practice have been identified. In conclusion it was shown that there are wider opportunities for teachers to offer and broadcast the modern model of educational environment, with the use of online learning based on information and telecommunication networks that requires from them highly developed expertise in organizing the individualization of learning for students and shaping their professional competencies, information culture, and digital literacy on this basis. Eventually, the authors have also proposed and justified conditions for stage wise digital transformation of educational content to be efficient.